Prenatal risk factors of wheezing at the age of four years in Tanzania. Issue 4 (1st April 2001) - Sunyer, J; Mendendez, C; Ventura, P J; Aponte, J J; Schellenberg, D; Kahigwa, E; Acosta, C; Antó, J M; Alonso, P L
Abstract : BACKGROUND: A study was undertaken to assess the interactions between prenatal exposures, early life infections, atopic predisposition, and allergen exposures in the development of wheezing up to the age of 4 years in a tropical region of Africa. METHODS: The study subjects comprised children born at the district hospital in Ifakara, Tanzania during a 1 year period who were participating in a trial of iron supplementation and malaria chemoprophylaxis during the first year of life and followed for up to 4 years. From this group of subjects, 658 (79%) participated in the interview at 18 months and 528 (64%) in a second interview at 4 years. Wheezing was measured with the ISAAC questionnaire. A hospital based inpatient and outpatient surveillance system was set up to document all attendance by study children for any cause, including episodes of clinical malaria and lower respiratory tract infections. Total IgE levels and malaria parasites were measured in maternal and cord blood. Total IgE was also measured at 18 months of age. Indoor environmental levels of Der p I and Fel d I were determined using an enzyme linked immunosorbent assay at the same time as the interview at the age of 18 months. RESULTS: The prevalence of wheezing at 4 years is common in Ifakara (14%, range 13–15%). The presence of malaria parasites in cord blood (odds ratio, OR = 6.84, 95% CI 1.84 to 24.0) and maternal asthma (OR = 8.47, 95% CI 2.72 to 26.2) were positively associated with wheezing at the age of 4 years, and cord blood total IgE was negatively associated (OR = 0.24, 95% CI 0.07 to 0.85) (all p<0.05). Parasitaemia at birth was not related to total IgE levels in cord blood (p=0.6). Clinical episodes of malaria during infancy were not associated with wheezing, and nor were levels of indoor aeroallergens. CONCLUSION: These findings suggest that events occurring during pregnancy may play a role in the future appearance of wheezing, although the results must be interpreted with caution because of the small numbers studied.